1999
DOI: 10.1073/pnas.96.20.11648
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of endothelial nitric oxide synthase to the penis augments erectile responses in the aged rat

Abstract: Nitric oxide (NO), a mediator involved in penile erection, is synthesized by the nitric oxide synthase (NOS) family of enzymes. It has been shown that NOS activity decreases with age. To determine whether adenoviralmediated overexpression of endothelial NOS (eNOS) could enhance erectile responses, we administered a recombinant adenovirus containing the eNOS gene (AdCMVeNOS) into the corpora cavernosum of the aged rat. Adenoviral expression of the ␤-galactosidase reporter gene was observed in cavernosal tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
126
0
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 26 publications
7
126
0
8
Order By: Relevance
“…17 However, in that study we used an adenovirus which had limited activity of expression of the eNOS gene, requiring repeated injections into the penis, which in turn could injure the vascular smooth muscle cells of the penis or, more importantly, cause a host-immune response. In the present study, instead of the cytomegalovirus promoter, we utilized the rous sarcoma promoter, which has been shown to exhibit a longer sustained duration of expression of a desired gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, in that study we used an adenovirus which had limited activity of expression of the eNOS gene, requiring repeated injections into the penis, which in turn could injure the vascular smooth muscle cells of the penis or, more importantly, cause a host-immune response. In the present study, instead of the cytomegalovirus promoter, we utilized the rous sarcoma promoter, which has been shown to exhibit a longer sustained duration of expression of a desired gene.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab demonstrated enhanced erectile response to cavernosal nerve stimulation in aged rats after adenoviral gene transfer of eNOS. 17 However, in this study, the expression of eNOS in the penis was limited to only 5 days. In the present study, our aim was to investigate the effect of adenoviral gene transfer of eNOS using a different promoter which exhibits a longer duration of expression of eNOS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that in vivo gene transfer with adenoviral vectors encoding eNOS and nNOS can reverse age-related ED in experimental animal models. [17][18][19][20] Additionally, overexpression of eNOS in the aged penis results in an increase in both cavernosal NOS activity and cGMP formation. 17,18,21 In the present study, we used the streptozotocin (STZ)-diabetic rat model that represents a model of type I DM.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that NO signals the biochemical mechanism of corpus cavernosal tissue relaxation established an essential foundation for the development of phosphodiesterase-5 inhibitor therapy for the therapeutic management of erectile dysfunction (ED). Additional translational efforts to harness the potential of this molecule for therapeutic purposes have suggested other possible therapies including pharmacologic NO precursors or actual NO donors, [1][2][3] NO-based gene therapy, 4,5 derivatives of NO synthase (NOS)-associated regulatory proteins, 6 and compounds targeting other components of the NO-based signal transduction pathway. 7,8 Ongoing basic scientific investigation of NO biology has revealed new concepts regarding the regulatory roles of this chemical, particularly those pertaining to mechanisms of activating NOS which synthesizes NO.…”
Section: Introductionmentioning
confidence: 99%